Antibacterial potency of acyclic diester, oleic acid, and β-amyrin tetradecanoate from Acacia lahai and Leucas calostachys against antibiotic-resistant bacteria - Kimutai, Nicholas Kogo; Ogutu, Philip A.; Kamau, Rahab; Mutai, Charles (Frontiers in Microbiology, 2025)
IntroductionThe increase in antibiotic-resistant microorganisms has led to the search of new and effective antimicrobial agents. Natural products from plants may, therefore, serve as alternative sources of substances for the treatment of these infections. Traditional practitioners use concoctions of Acacia lahai and Leucas calostachys extracts for the treatment of wounds, skin diseases, coughs, ulcers, and intestinal ailments. This is because they are rich in potent antibacterial compounds. The objective of this study was to isolate bioactive compounds from A. lahai and L. calostachys using bioassay-guided fractionation.MethodsBioactivity testing was performed against selected microbes using disc diffusion and broth microdilution methods, as recommended by the Clinical and Laboratory Standards Institute (CLSI). Pure compounds were isolated using chromatographic procedures, and their structures were elucidated based on 1D and 2D NMR analyses.ResultsFractionation yielded two fatty acids, namely, 5-(2, 5-dimethylhexyl) 1-isopentyl 3-hydroxy-2-methylpentanedioate (acyclic diester) (1) and cis oleic acid (2) from A. lahai and L. calostachys, respectively. In addition, L. calostachys yields terpenoid β-amyrin tetradecanoate (3). The three compounds were selectively active against the tested microorganisms, with minimum inhibitory concentrations (MICs) of 25.0 mg/mL and 100.0 mg/mL shown by cis oleic acid and β-amyrin tetradecanoate against Staphylococcus aureus, respectively. These two compounds were isolated and tested for antibacterial activity against this plant for the first time. In addition, an acyclic diester named 5-(2, 5-dimethylhexyl) 1-isopentyl 3-hydroxy-2-methylpentanedioate (2) was isolated and screened for antibacterial activity for the first time from the extracts of Acacia lahai.ConclusionAcacia lahai and Leucas calostachys extracts and compounds showed antibacterial activity against multidrug-resistant bacteria. This study provides valuable insights into the development of effective antimicrobial agents.